PENGEMBANGAN EKONOMI LOKAL MELALUI INDUSTRI HALAL: STUDI EMPIRIS UMKM DI KABUPATEN BONE - Anggryani, Lisa; Hayati HS, Husna; Amal, A. Arsy Ramlan; Karyono, Otong (Politeknik Bisnis Indonesia, 2024)
The local economy is a topic that is widely discussed because of its importance in economic growth, because it is local, one of the sectors that supports it is the MSME (Micro, Small and Medium Enterprises) sector. In line with this, the global halal industry has experienced growth in several years final. The local economy and the halal industry are two interesting things to research, therefore this research contributes to the literature with a focus on local economic empowerment through the development of the halal industry. This research is a field research study with an economic approach and the data was collected using interviews with 5 people responded, the results of the research show that the development of the MSME halal industry in Bone Regency shows a positive trend with an increase in the number of MSMEs and the average income of the sector. MSME players show commitment to halal principles, government support is considered key, and even though they have not implemented many specific marketing strategies, they have succeeded in utilizing social media. In the context of local economic empowerment, the Bone Regency government supports the halal industry through tax incentives, collaboration with the private sector, and active promotion. Thus, it is hoped that the potential of the halal industry in Bone Regency will continue to have a positive impact on local economic growth and job creation, making this area the center of a competitive halal industrial cluster.